Asymptotic Degree Distribution of a Kind of Asymmetric Evolving Network - Zhimin Li; Zhaolin He; Chunhua Hu (Abstract and Applied Analysis)
We propose a kind of evolving network which shows tree structure. The model is a combination of preferential attachment model and uniform model. We show that the proportional degree sequence pkk>1 obeys power law, exponential distribution, and other forms according to the relation of k and parameter m.